Daniellia oliveri Leaf Extracts as an Alternative to Antibiotic Feed Additives in Broiler Chicken Diets: Meat Quality and Fatty Acid Composition - John Alagbe (CV. Literasi Indonesia, 2021)
The objective of the study was to examine the effect of feeding different levels of Daniellia oliveri leaf extract (DOFE) on the meat quality and fatty acid composition of broiler chicks. A total of 375 one –day old broiler chicks were randomly assigned into five dietary treatments of seventy-five birds per group; each group was further divided into 5 replicates consisting of 15 chicks each. The dietary treatments include a control diet-fed 1.25 g/litre Oxytetracycline (T1), T2, T3, T4 and T5 were fed DOFE at 20 ml, 40ml, 60ml and 80 ml/liter respectively. Basal diet was formulated to meet the nutritional requirements of birds according to NRC (1994), feed and water were given ad libitum and the experiment lasted for 56 days. Result obtained showed that Daniellia oliveri leaf contained Dry matter (89.11%), crude protein (18.95%), crude fibre (13.11%), ether extract (4.78%), ash (6.10%), neutral detergent fibre (28.10%), and acid detergent fibre (47.50%). Significant differences (P<0.05) were observed in the proximate composition of the breast meat. Total saturated fatty acid (TSFA), total unsaturated fatty acid (TUFA), and omega-6/omega -3 ratio (n-6: n-3) values were significantly influenced (P<0.05) by DOFE. Birds in T5 had the highest TUFA value of 77.87 % followed by T4 (72.45%), T3 (66.43%), T2 (61.94 %), and T1 (41.47%) respectively. While T1 (44.71%) had the highest value of TSFA (P<0.05) relative to other treatments. The atherogenic index was significantly (P<0.05) different among the treatments, the value increases as the level of DOFE increased. It was concluded that feeding DOFE to birds at 80 ml/liter highly influenced the composition of fatty acid and meat quality of animals without any negative effect on their general performance.